2020
DOI: 10.1177/0193945920973025
|View full text |Cite
|
Sign up to set email alerts
|

Use of PADIS Assessment Tools by Critical Care Nurses: An Integrative Review

Abstract: The purpose of this integrative review was to evaluate the literature from January 2013 to April 2020 and to explore critical care nurses’ perspectives of and intent to use recommended Pain, Agitation/Sedation, Delirium, Immobility, and Sleep Disruption (PADIS) patient assessment tools in adult critical care units. A literature search was performed with a total of 47 studies included in the final analysis for this review. The studies’ data were organized and further reduced based on The Reasoned Action Approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 75 publications
(357 reference statements)
0
5
0
Order By: Relevance
“…These findings are consistent with previous studies that highlight barriers to implementing practice guidelines related to nurse attitudes, beliefs, role clarity, and workload burden. [9][10][11]15 However, research has found that evidence-based care like the use of PADIS assessment tools can improve attention to patients, individualized care, and communication among team members but requires support from the entire care team. 15 PADIS care is dependent on more than 1 nurse's decision-making but encompasses moral attitude, ethical leadership, empowerment for ethical practice, and establishing and supporting a moral community.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are consistent with previous studies that highlight barriers to implementing practice guidelines related to nurse attitudes, beliefs, role clarity, and workload burden. [9][10][11]15 However, research has found that evidence-based care like the use of PADIS assessment tools can improve attention to patients, individualized care, and communication among team members but requires support from the entire care team. 15 PADIS care is dependent on more than 1 nurse's decision-making but encompasses moral attitude, ethical leadership, empowerment for ethical practice, and establishing and supporting a moral community.…”
Section: Discussionmentioning
confidence: 99%
“…Others do not or cannot because of many personal, environmental, and perhaps ethical reasons. 10,11,[13][14][15] Critical care nurses are typically equipped to recognize the ethical implications of higher-risk clinical situations like end-of-life decisions and the allocation of scarce resources. However, the ability to recognize moral conflict and ethical consequence (ie, ethical sensitivity) of everyday tasks included in PADIS care like mobilizing a patient or appropriate medication administration is not often recognized or discussed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the patient in intensive care is not always able to communicate verbally, the CAM-ICU was adapted to screen intubated or artificially ventilated patients (Cribbin, 2018). The results of this scale are limited by the binomial approach of the evaluation of delirium, and the fact that it is a one-point-in-time assessment (Waterfield, Barnason 2021). The Neelon and Champagne (NEECHAM) Confusion Scale was developed a few years later, based on daily nursing practice: the nurses' 24-hour assessment of the level of processing information, the level of behavior, and the physiological condition rate.…”
Section: Introductionmentioning
confidence: 99%